Penanggulangan Stunting Melalui Peningkatan Partisipasi Masyarakat dengan Sosialisasi Pentingnya Gizi Anak di Kelurahan Lalung, Kecamatan Karanganyar, Kabupaten Karanganyar, Jawa Tengah - Rais, Wakit Abdul; Sakti, Prima Putra; Utami, Pratiwi Noor; Oktaviana, Stia Ayu; Dzumar, Sahmurah Sahdah; Yunita, Novita Mela; Effendi, Janeth Christy; Ramadhani, Sekarningtyas Adita; Titovandaru, Wisanggeni; Siburian, Tesalonika Oktavia; Paleta, Jessica (Society : Jurnal Pengabdian Masyarakat, 2023)
Posyandu is a community-based integrated health service. To reduce the rate of malnutrition, this government system tracks the development and nutritional health of toddlers. The Posyandu program was carried out in Lalung, Karanganyar Regency, Central Java by Group 109 of KKN UNS. This program involved local health workers, Posyandu’s volunteers, and was assisted by KKN students that were attended by the parents and their toddlers. The services offered included monitoring of weight, height, arm and head circumference measurements, growth and development evaluation and counseling, distribution of vitamin A, and provision of child nutrition. This community service program aimed to monitor children's growth and development and prevent stunting. The method used in this program was direct counseling and distribution of leaflets on the importance of child nutrition for parents of babies and toddlers. The findings showed that parents and kids both had a good understanding of how to provide for a child's nutritional needs and how to prevent stunting. The outcomes of this Posyandu program have a positive impact on the community and are beneficial to monitor the growth of toddlers and prevent stunting. This result of the program is expected to make the parents of toddlers consistently participate in monthly Posyandu activities and fulfill their child's nutrition properly in hopes that stunting can be prevented.